Answer:
Step-by-step explanation:
This can be broken down into a square and a rectangle.
A=5(5)+(12)(8-5)
A=25+12(3)
A=25+36
A=61 u^2
Answer:
x = 3 ± 2![\sqrt{2}](https://tex.z-dn.net/?f=%5Csqrt%7B2%7D)
Step-by-step explanation:
given
x² - 6x + 1 = 0 ( subtract 1 from both sides )
x² - 6x = - 1
To complete the square
add (half the coefficient of the x- term)² to both sides
x² - 6x + (- 3)² = - 1 + (- 3)²
x² - 6x + 9 = - 1 + 9
(x - 3)² = 8 ( take the square root of both sides )
x - 3 = ±
= ± 2
( add 3 to both sides )
x = 3 ± 2![\sqrt{2}](https://tex.z-dn.net/?f=%5Csqrt%7B2%7D)
I guess B. That statement is grammatically incorrect.
Answer:
C
Step-by-step explanation:
< open circle, not ≤
Answer:
It would be D
Step-by-step explanation:
All the coordinates are divided by half.